Histoire de la formation en architecture de paysage à l’Université de Montréal - Nicole Valois; Ron Williams (Projets de Paysage)
For more than fifty years, the École d’architecture de paysage of the University of Montreal has offered one of the main educational programms in landscape architecture in Canada. As the only French-language school in the Americas, it has trained several generations of teachers and professionals who have made their mark on the history of environmental design in Quebec and Canada. The article recounting the history of this institution is based on the archives of the University of Montreal and interviews conducted with six professors of the first generation. This allowed us to identify the important periods of the School’s development and the distinctive historical aspects of its curricula and academic contributions. Created in the progressive wave in Quebec in the 1960s and the great social and ecological movements of that period, the School has undergone several profound transformations over the past five decades as it has continually adapted to the renewed challenges presented by the landscape and the profession. The following account sheds a unique light on this topic and hopefully provides the framework for a narrative to be continued.